Diatoms as a sea-ice proxy : improving the accuracy of sea-ice reconstruction by re-analysing the northern North Atlantic training set for Fragilariopsis oceanica, Fragilariopsis reginae-jahniae and Fossula arctica, in addition to the chrysophyte cyst Archaeomonas sp. - Redmond Roche, Benjamin Heikki (Helsingin yliopisto, 2019)
Significant changes in sea-ice variability have occurred in the northern North Atlantic since the last deglaciation, resulting in global scale shifts in climate. By inferring the dynamic changes of palaeo seaice to past changes in climate, it is possible to predict future changes in response to anthropogenic climate change. Diatoms allow for detailed reconstructions of palaeoceanographic and sea-ice conditions, both qualitatively, using information of species ecologies and quantitatively, via a transfer function based upon diatom species optima and tolerances of the variable to be reconstructed. Three diatom species comprising a large portion of the training set are proxies for the presence of sea ice: Fragilariopsis oceanica, Fragilariopsis reginae-jahniae and Fossula arctica, have currently been grouped into one species – F. oceanica – in the large diatom training set of the northern North Atlantic region. The clustering of the species may result in an imprecise reconstruction of sea ice that does not take into account all the available ecological information. The proportions of the three species were recounted from the original surface sediment slides alongside the additional chrysophyte cyst Archaeomonas sp. and statistically analysed using Canoco and the R software package eHOF. A core from Kangerlussuaq Trough comprising the Late Holocene (~690–1498 Common Era) was also recounted and analysed using C2. The separated diatom species and chrysophyte cyst Archaeomonas sp. exhibited different relationships to both sea-ice concentration (aSIC) and sea surface temperature (aSST). The separated F. oceanica is a ‘cold-mixed’ water species occurring at cold aSST and both low and high aSIC. High abundances occur in the marginal ice zone (MIZ) where surficial meltwater is high during the spring bloom, with additional inputs from glacial meltwaters nearshore. F. reginae-jahniae is a sea-ice associated species related to cold aSST and high aSIC. High abundances occur in the low salinity Arctic Water dominated MIZ which ...